Reimagining English language learning: a systematic review of AI integration in classroom practice (2019–2024) - Ibrahim Brian, Muhammad Shyazzwan (Universiti Teknologi MARA, Kedah, 2025)
This Systematic Literature Review (SLR) examines the integration of Artificial Intelligence (AI) in English Language Learning (ELL) with the aim of reimagining classrooms as creative, inclusive, and technology-enhanced spaces. Based on 48 peer-reviewed empirical studies published between 2019 and 2024, the review explores how AI tools, particularly Natural Language Processing (NLP), Intelligent Tutoring Systems (ITS), and generative AI, support personalized learning, increase engagement, and strengthen skill development among English language learners. Grounded in constructivist and socio-cultural theories, these technologies promote collaboration, creativity, and learner autonomy through adaptive learning pathways and real-time feedback. While the benefits are evident, the review also highlights ongoing challenges. These include limited teacher preparedness, ethical concerns such as data privacy and algorithmic bias, and a lack of research into the long-term, scalable use of AI, particularly in under-resourced or marginalized educational contexts. To address these issues, the study emphasizes the need for professional development guided by the Technological Pedagogical Content Knowledge (TPACK) framework, as well as clear policy measures that promote ethical, equitable, and transparent AI integration. A conceptual model is proposed, aligning AI capabilities with pedagogical goals and ethical safeguards. This model serves as a practical guide for educators and stakeholders aiming to implement AI-enhanced pedagogies responsibly. Ultimately, the study underscores the need for interdisciplinary collaboration among educators, policymakers, and technology developers to foster sustainable and inclusive learning environments. Although AI holds great potential to transform English language education, its implementation must prioritize ethics, transparency, and the well-being of both learners and teachers.